A Corpus-based Diachronic Developmental Features of Semantic Generalization of the English Learners in China - Changzhong Shao (Forest Chemicals Review)
Based on a corpus, this paper explores the diachronic developmental features of semantic generalization by taking indefinite pronouns as an example in the writing of academic papers by the undergraduate, graduate and doctoral English learners in China. The results of the comparative analysis with the corpus of journal authors show that the overall frequency of semantic generalizations is higher, while the frequency of reasonable generalizations is lower. In the undergraduate stage, there are more use of semantic generalization markers, while in the master stage, the use of semantic generalization markers is much lower, and in the doctoral stage, it is closer to the use of journal authors. In terms of specific categories, the overall generalization continues to decrease, while the individual generalization continues to increase, and the partial generalization presents ups and downs. The research reveals that the regular features of the fluctuating decline of semantic generalization in the process of English socialization.